PEMANFAATAN SISTEM INFORMASI BERBASIS SOFTWARE DI MTS TAHFIDZUL QUR’AN AL IMAM ASHIM MAKASSAR - Farzana Fadillah Noer; Damopolii, Muljono; Hasan, Mardhiah (Idaarah: Jurnal Manajemen Pendidikan, 2023)
The use of software-based information systems at MTs Tahfizhul Qur'an Al Imam Ashim Makassar can be driven by the specific needs and vision of the school. Through technology integration, schools can optimize their educational and administrative processes to improve educational quality and operational efficiency. The aim of this research is to analyze the implementation and benefits obtained through the use of software-based information systems in the management and development of educational institutions. This research uses descriptive research methods. Data was obtained through direct observation of system use, interviews with school staff, and analysis of documents related to the use of information systems at MTs Tahfizhul Qur'an Information Al Imam Ashim Makassar. The research results show that the use of software-based information systems, such as EMIS, SIMPATIKA, RDM, EDM, ERKAM, and VERVAL, provides a number of significant benefits for MTs Tahfizhul Qur'an Al Imam Ashim Makassar. The use of software-based information systems at MTS Tahfizhul Qur'an Al Imam Ashim Makassar makes a positive contribution in increasing the operational efficiency of the institution, improving decision making, and improving the quality of educational services. It is hoped that this research can provide insights and recommendations for other educational institutions that wish to utilize software-based information systems and the integration of different information systems.